Carnosine activates cellular stress response in podocytes and reduces glycative and lipoperoxidative stress - Scuto, Maria; Trovato, Angela; Modafferi, Sergio; Polimeni, Alessandra; Pfeffer, Tilman; Weigand, Tim; Calabrese, Vittorio; Schmitt, Claus P.; Peters, Verena (Biomedicines, 2020)
Carnosine improves diabetic complications, including diabetic nephropathy, in in vivo models. To further understand the underlying mechanism of nephroprotection, we studied the effect of carnosine under glucose-induced stress on cellular stress response proteins in murine immortalized podocytes, essential for glomerular function. High-glucose stress initiated stress response by increasing intracellular heat shock protein 70 (Hsp70), sirtuin-1 (Sirt-1), thioredoxin (Trx), glutamate-cysteine ligase (gamma-glutamyl cysteine synthetase; γ-GCS) and heme oxygenase-1 (HO-1) in podocytes by 30–50% compared to untreated cells. Carnosine (1 mM) also induced a corresponding upregulation of these intracellular stress markers, which was even more prominent compared to glucose for Hsp70 (21%), γ-GCS and HO-1 (13% and 20%, respectively; all p < 0.001). Co-incubation of carnosine (1 mM) and glucose (25 mM) induced further upregulation of Hsp70 (84%), Sirt-1 (52%), Trx (35%), γ-GCS (90%) and HO-1 (73%) concentrations compared to untreated cells (all p < 0.001). The glucose-induced increase in 4-hydroxy-trans-2-nonenal (HNE) and protein carbonylation was reduced dose-dependently by carnosine by more than 50% (p < 0.001). Although podocytes tolerated high carnosine concentrations (10 mM), high carnosine levels only slightly increased Trx and γ-GCS (10% and 19%, respectively, compared to controls; p < 0.001), but not Hsp70, Sirt-1 and HO-1 proteins (p not significant), and did not modify the glucose-induced oxidative stress response. In podocytes, carnosine induced cellular stress tolerance and resilience pathways and was highly effective in reducing high-glucose-induced glycative and lipoperoxidative stress. Carnosine in moderate concentrations exerted a direct podocyte molecular protective action.
Gesehen am 26.08.2020